Protocol for Deferral of Consent in Acute Stroke Trials. (7th February 2023) - Faris, Hannah; Dewar, Brian; Fedyk, Mark; Dowlatshahi, Dar; Menon, Bijoy; Swartz, Richard H.; Hill, Michael D.; Shamy, Michel
Abstract : The challenges of conducting hyperacute stroke research and obtaining informed consent have been increasingly recognized within the stroke research community in recent years. Deferral of consent, in which a patient is enrolled in a trial and then provides consent at some point thereafter, is increasingly used to enroll patients into hyperacute stroke trials in Canada and Europe, although it is not permitted in the United States. Deferral of consent offers several potential advantages—quicker door-to-randomization, increased enrolment, decreased selection bias—but these must be balanced against the risk of enrolling patients against their wishes. We seek to minimize the attendant risks of deferral of consent by offering practical guidance regarding how to conduct acute stroke trials using deferral of consent. Building on existing guidelines and recent experiences with deferral of consent in acute stroke trials, we have developed a protocol for the use of deferral of consent that aims to maximize patient involvement while minimizing ethical and scientific risks.